2022
DOI: 10.1002/fam.3055
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation on the characteristics of lateral smoke extraction in the immersed road tunnel

Abstract: A series of numerical simulations are carried out to explore the characteristics of the smoke layer in an immersed road tunnel with the lateral smoke extraction system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…In this study, the smoke extraction velocity of the lateral exhaust vent was set to 8 m/s based on the previous studies. 21,26 Four different aspect ratios of lateral exhaust vent (As ¼ W vent =H vent , 1:1, 1:2, 2:1 and 3:1) were investigated, as illustrated in Figure 2B. The area of lateral smoke exhaust vent positioned on the tunnel sidewall is 2 m 2 , referring to the practical case.…”
Section: Fire Scenariomentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the smoke extraction velocity of the lateral exhaust vent was set to 8 m/s based on the previous studies. 21,26 Four different aspect ratios of lateral exhaust vent (As ¼ W vent =H vent , 1:1, 1:2, 2:1 and 3:1) were investigated, as illustrated in Figure 2B. The area of lateral smoke exhaust vent positioned on the tunnel sidewall is 2 m 2 , referring to the practical case.…”
Section: Fire Scenariomentioning
confidence: 99%
“…Also, it was proven that when the smoke barrier's inclined angle is 30 < θ ≤ 75 , a significantly improved smoke extraction efficiency can be achieved. 26 On the other hand, it is known that the immediate cause for plugholing is the adherent flow of fresh air, 21 as presented in Figure 1B.…”
Section: Introductionmentioning
confidence: 99%
“…This study used FDS simulation software, which is widely used in the field of fire simulation. 22,23 In practical engineering applications, the use of shield tunneling to construct circular tunnels has gradually replaced the early rectangular cross-section shape as a common phenomenon. Wu and Bakar 24 showed that the influence mechanism of tunnel section on fire smoke transport characteristics cannot be well demonstrated using only the physical parameter of tunnel height.…”
Section: Fds Modelmentioning
confidence: 99%
“…This study used FDS simulation software, which is widely used in the field of fire simulation 22,23 . In practical engineering applications, the use of shield tunneling to construct circular tunnels has gradually replaced the early rectangular cross‐section shape as a common phenomenon.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…In the FDS simulation, propane was selected as the fuel. According to the FDS manual and the research results of others, 26,27 the combustion heat of propane was set to 44715 kJ/kg, and the soot yield and CO yield were both set to 0.05. The soot yield and CO yield were directly affected by combustion and ventilation conditions, and a constant value was used here for simplicity 28 …”
Section: Fds Simulationmentioning
confidence: 99%